Accuracy of Cloudshine Gamma Dose Calculations in the CAP-88 Dispersion Model. Issue 4 (April 2017) - McNaughton, Michael W.; Gillis, Jessica M.; Ruedig, Elizabeth; Whicker, Jeffrey J.; Fuehne, David P.
Abstract : Abstract: The U.S. Environmental Protection Agency dispersion model, CAP‐88, calculates ground-level dose using the ground-level concentration and the semi-infinite cloud approximation. Doses can be underestimated for elevated plumes during stable atmospheric conditions at receptor locations within a kilometer downwind of a stack. The purpose of this paper is to identify when CAP‐88 calculations of gamma dose from cloudshine are inaccurate and provide estimates of the inaccuracy. The method used compares CAP‐88 estimates with Monte Carlo N-Particle (MCNP) estimates. Comparisons were made at distances of 800 m and 3, 000 m downwind of the stack and for plume heights from 0 to 50 m. For these conditions, the annual dose calculated by CAP‐88 is greater than or equal to that calculated by MCNP.